Combination Therapy of PPAR𝛾 Ligands and Inhibitors of Arachidonic Acid in Lung Cancer - Jordi Tauler; James L. Mulshine (PPAR Research)
Lung cancer is the leading cause of cancer death in the United States and five-year survival remains low. Numerous studies have shown that chronic inflammation may lead to progression of carcinogenesis. As a result of inflammatory stimulation, arachidonic acid (AA) metabolism produces proliferation mediators through complex and dynamic interactions of the products of the LOX/COX enzymes. One important mediator in the activation of the AA pathways is the nuclear protein PPAR𝛾. Targeting LOX/COX enzymes and inducing activation of PPAR𝛾 have resulted in significant reduction of cell growth in lung cancer cell lines. However, specific COX-inhibitors have been correlated with an increased cardiovascular risk. Clinical applications are still being explored with a novel generation of dual LOX/COX inhibitors. PPAR𝛾 activation through synthetic ligands (TZDs) has revealed a great mechanistic complexity since effects are produced through PPAR𝛾-dependent and -independent mechanisms. Furthermore, PPAR𝛾 could also be involved in regulation of COX-2. Overexpression of PPAR𝛾 has reported to play a role in control of invasion and differentiation. Exploring the function of PPAR𝛾, in this new context, may provide a better mechanistic model of its role in cancer and give an opportunity to design a more efficient therapeutic approach in combination with LOX/COX inhibitors.